ArgD of Mycobacterium tuberculosis is a functional N-acetylornithine aminotransferase with moonlighting function as an effective immune modulator - Iqra Bashir Nehvi; Neha Quadir; Mohd Khubaib; Javaid Ahmad Sheikh; Mohd Shariq; Krishnaveni Mohareer; Sharmistha Banerjee; Syed Asad Rahman; Nasreen Z. Ehtesham; Seyed E. Hasnain (Elsevier, 2022)
Mycobacterium tuberculosis (M. tuberculosis) encodes an essential enzyme acetyl ornithine aminotransferase ArgD (Rv1655) of arginine biosynthetic pathway which plays crucial role in M. tuberculosis growth and survival. ArgD catalyzes the reversible conversion of N-acetylornithine and 2 oxoglutarate into glutamate-5-semialdehyde and L-glutamate. It also possesses succinyl diaminopimelate aminotransferase activity and can thus carry out the corresponding step in lysine biosynthesis. These essential roles played by ArgD in amino acid biosynthetic pathways highlight it as an important metabolic chokepoint thus an important drug target. We showed that M. tuberculosis ArgD rescues the growth of ΔargD E. coli grown in minimal media validating its functional importance. Phylogenetic analysis of M. tuberculosis ArgD showed homology with proteins in gram positive bacteria, pathogenic and non-pathogenic mycobacteria suggesting the essentiality of this protein. ArgD is a secretory protein that could be utilized by M. tuberculosis to modulate host innate immunity as its moonlighting function. In-silico analysis predicted it to be a highly antigenic protein. The recombinant ArgD protein when exposed to macrophage cells induced enhanced production of pro-inflammatory cytokines TNF, IL6 and IL12 in a dose dependent manner. ArgD also induced the increased production of innate immune effector molecule NOS2 and NO in macrophages. We also demonstrated ArgD mediated activation of the canonical NFkB pathway. Notably, we also show that ArgD is a specific TLR4 agonist involved in the activation of pro-inflammatory signaling for sustained production of effector cytokines. Intriguingly, ArgD protein treatment activated macrophages to acquire the M1 phenotype through the increased surface expression of MHCII and costimulatory molecules CD80 and CD86. ArgD induced robust B-cell response in immunized mice, validating its antigenicity potential as predicted by the in-silico analysis. These properties of M. tuberculosis ArgD signify its functional plasticity that could be exploited as a possible drug target to combat tuberculosis.